2015
DOI: 10.1073/pnas.1410400112
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived antifungal agent poacic acid targets β-1,3-glucan

Abstract: A rise in resistance to current antifungals necessitates strategies to identify alternative sources of effective fungicides. We report the discovery of poacic acid, a potent antifungal compound found in lignocellulosic hydrolysates of grasses. Chemical genomics using Saccharomyces cerevisiae showed that loss of cell wall synthesis and maintenance genes conferred increased sensitivity to poacic acid. Morphological analysis revealed that cells treated with poacic acid behaved similarly to cells treated with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
136
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(143 citation statements)
references
References 62 publications
6
136
0
1
Order By: Relevance
“…Chemical genomic analysis of these hydrolysates was performed as described previously using a collection of ~3500 yeast deletion mutants [19, 36]. 200 µL cultures of the pooled collection of S. cerevisiae deletion mutants were grown anaerobically in the different versions of ACSH and ASGH, or yeast-rich medium (YPD, 20 g/L peptone, 10 g/L yeast extract, 20 g/L glucose), diluted 1:1 with sterile water, in triplicate for 48 h at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical genomic analysis of these hydrolysates was performed as described previously using a collection of ~3500 yeast deletion mutants [19, 36]. 200 µL cultures of the pooled collection of S. cerevisiae deletion mutants were grown anaerobically in the different versions of ACSH and ASGH, or yeast-rich medium (YPD, 20 g/L peptone, 10 g/L yeast extract, 20 g/L glucose), diluted 1:1 with sterile water, in triplicate for 48 h at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The barcode counts for each yeast deletion mutant in the hydrolysates were normalized against the synthetic hydrolysate control (SynH2.1) [16] in order to define sensitivity or resistance of individual strains (chemical genetic interaction score). The pattern of genetic interaction scores for all mutant strains represents the chemical genomic profile or “biological fingerprint” of a sample [19, 36]. The clustergram of the chemical genomic profiles was created in Cluster 3.0 [37], and visualized in Treeview (v1.1.6r4) [38].…”
Section: Methodsmentioning
confidence: 99%
“…However, some destabilization of the cell wall structure may occur, without any visual effect by fluorescent labeling, due to its β- N -acetyl- D -glucosaminidase activity, at the end of the chitin polymer. In fact, the absence of visual damages at the cell wall does not imply a fully operational and structured wall, as the same can be observed even with cell wall-targeting drugs (Piotrowski et al, 2015). This might explain why the cell wall remained visually intact with calcofluor white staining, while the cells were becoming metabolically inactive, or even dead.…”
Section: Discussionmentioning
confidence: 93%
“…Propidium iodide may also be used as an indicator of cell leakage, or cell permeability (Piotrowski et al, 2015). In any case, it was here demonstrated that BCO induces cell membrane damage in C. albicans , and this surely contributes to its inhibitory and/or lethal effect on cells.…”
Section: Discussionmentioning
confidence: 99%
“…and bran. According to the literature, ferulic acid and its derivatives demonstrate extensive biological effects, such as antiviral, antibacterial and antitumor activities . Meanwhile, the literature shows that ferulic acid ester derivative activities are superior to those of ferulic acid amide derivatives .…”
Section: Introductionmentioning
confidence: 99%